Incipient regressive evolution of the circadian rhythms of a cave amphipod - Luis Espinasa; Emily Collins; Anthony Finocchiaro; Joseph Kopp; Jenna Robinson; Jennifer Rutkowski (Subterranean Biology, 2016)
The habitat of cave-adapted organisms is characterized by complete darkness and in some instances, an apparent lack of environmental distinction between day and night. It is unclear if cave-adapted organisms retain circadian rhythms that can be light-entrained. Stygobromus allegheniensis (Allegheny Cave Amphipod) is an eyeless troglobitic crustacean found in caves located in the Northeastern region of the United States. Two cave populations were examined for evidence of light-entrained circadian rhythms. The first population inhabits a small tectonic cave (Ice Caves, Sam’s Point Preserve, NY) and the second (Clarksville Cave, Clarksville, NY) inhabits a long cave system in limestone rock. Experiments conducted in both the field and the laboratory suggest that the capacity to exhibit motor rhythms has been conserved in at least some individuals of both populations. Nonetheless, their motor activity rhythms have high variability of period length between individuals and do not appear to be light-entrainable. It is thus proposed that in this species, light-entrainable circadian rhythms controlling motor activity have undergone incipient regressive evolution.